Individual and joint effects of exposure to multiple organophosphate esters and the risk of depression in adults: Differences in sex, age, and physical activity - Qingmiao Wei; Jiyun Wei; Jun Liang (Ecotoxicology and Environmental Safety)
Depression, a severe mental disorder, is a prominent cause of global disability and worldwide. Organophosphate esters (OPEs) are neuron-disrupting chemicals that potentially cause depression. However, the effects of OPEs on depression remain unclear. We aimed to assess the associations among five OPE levels in urine and depression by using NHANES 2011–2018. Generalized linear model, quantile g-computation (Qgcomp), and Bayesian kernel machine regression (BKMR) were utilized to assess the effects of OPEs on depression. In the generalized linear model, a one-unit increase in the natural logarithm (ln) of the urinary level of diphenyl phosphate (DPHP) was related to a respective ln-increase of 0.038(95 % CI: 0.002, 0.074) in the square root-transformed depression score, and each unit increase in the ln values of DBUP levels was related to a 1.163-fold (95 % CI: 1.013, 1.334) increase in the odds of depression in the crude models. Additionally, the effects of OPE exposure on depression and depression scores were pronounced in females, younger individuals, and physically inactive individuals. RCS revealed a U-shaped relationship between bis (1,3-dichloro-2-propyl) phosphate (BDCPP) level and the risk of depression (P-nonlinear=0.023). BKMR suggested that BDCPP and DPHP levels had a U-shaped relationship with the risk of depression. In the Qgcomp model, each one quartile increment in a mixture of OPEs was related to a 0.186 increase (95 % CI: 0.034, 0.338) in the depression score. In the BKMR, a positive association was noted between OPE mixtures and depression scores, and a U-shaped nonlinear association was noted between OPE mixtures and the risk of depression. The results indicated that exposure to single and multiple OPEs can increase the risk of depression in adults, indicating nonmonotonic dose–response relationships. Potential sex specific, age dependent, and exercise-related effects were found.